In vitro micropropagation protocol for Vanda hybrids with clonal fidelity analysis - Rosemol Baby (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2016)
Vanda orchids are one of the most sought after orchids in the international as well as domestic flower markets both as cut flower and potted plants. It is a monopodial orchid with vividly coloured, loosely arranged large beautiful flowers which has a long shelf life. Presently, many Vanda hybrids are becoming prominent even in the home gardens. However the present scenario of importing these hybrids from Thailand, Singapore and Malaysia to meet the Indian demands throws light on the need for developing an efficient propagation method for Vanda orchids. One of the major limiting factors for its spread and large scale cultivation in India is the non-availability of good quality and true to type planting material at a reasonable price. As the demand is more for the true to type plants, micropropagation is mostly recommended for orchid propagation. Hence this study was undertaken to develop an efficient micropropagation protocol for two Vanda hybrids namely Dr.Anek and Sansai Blue and to check the variability between the parents and regenerated plantlets. The different explants tested to initiate the cultures were leaf, root, stem and inflorescence segments. Initially the surface sterilization procedure was standardized for the explants. The results of the experiment showed that treating the explants with 0.1 per cent carbendazim for 20 minutes, followed by 70 per cent ethanol for 5 minutes and 0.1 per cent mercuric chloride for 5 min effectively reduced the microbial contamination with highest percentage of explant survival.Trial was made to initiate cultures using eight reported media compositions. The study showed positive results for inflorescence segments inoculated on to 1/2 MS + 10 mg l-1 BA+ 2 mg l-1 TDZ+30 g l-1 sucrose+7.5 g l-1agar + 250 mg l-1 cefotaxime as observed as direct shooting of the dormant buds. About 80 per cent and 60 per cent culture establishment was brought about in Dr. Anek and Sansai Blue respectively in 9 weeks. The established cultures successfully produced multiple shoots on MS+4.5 ml l-1BA +30 g l-1 sucrose + 7.5 g l-1 agar + 250 mg l-1 cefotaxime both when inoculated with and without the stalk in about 100 days of inoculation of explant. The micro-shoots from cultures without stalk were further transferred to hormone free basal MS media for elongation. Elongated shoots of about 4 cm were transferred to rooting media with a composition of MS + 0.5 mg l-1 NAA + 1 mg l-1 IAA +30 g l-1 sucrose +7.5 g l-1agar + 250 mg l-1 cefotaxime for better rooting of the regenerants. The percentage of rooting was observed to be 72.41 per cent for Dr. Anek and 70.37 per cent in Sansai Blue. The rooted plantlets with ample number of healthy roots were planted outm in small earthen pots with charcoal, coconut husk and brick pieces. These were successfully hardened in net house of 50 per cent shade and showed a hundred percent plantlet survival.Good quality DNA isolated from the mother plants and their respective clones using Rogers and Bendich procedure were analyzed for the clonal fidelity. ISSR analysis was done using 5 UBC (University of British Columbia) primers such as UBC 808, UBC 811, UBC 826, UBC 835 and UBC 841. An average of 8 to 9 bands was obtained from all primers in Dr. Anek and Sansai Blue. Out of 5 primers, UBC 808 and UBC 835 generated polymorphic bands in two clones of Dr. Anek. For Sansai Blue, all five primers generated monomorphic bands for all the mother plants and their respective clones analyzed. The per cent polymorphism in Dr. Anek was calculated to be 1.11 per cent whereas for Sansai Blue, there was no polymorphism detected revealing the true to type nature of the clones. The results showed that the identified protocol for in vitro regeneration of selected Vanda hybrids is a viable protocol since there were no changes in the banding pattern observed in tissue culture plants as compared with that of mother plant. Hence it can be concluded that the developed micropropagation protocol can be used for commercial production of Vanda hybrids without much risk of genetic instability. ISSR markers were effective to evaluate the genetic stability of the clones regenerated from the mother plants by the identified protocol.